Speed Control on a 3-Phase Induction Motor with an IFOC System Using a PI Controller: Simulation Approach - Reza Sarwo Widagdo; Ardianik; Imam Suri Tauladan; Aris Heri Andriawan (International Journal of Electrical, Energy and Power System Engineering)
The use of three-phase induction motors as electric drives is very popular due to several advantages, such as lower cost, robust construction, and minimal maintenance requirements. Despite these advantages, induction motors possess non-linear characteristics, making them challenging to regulate using conventional control methods. To overcome these challenges, several advanced control techniques have been developed, one of which is Indirect Field Oriented Control (IFOC). IFOC enables independent control of the motor’s magnetic field and torque by transforming the stator currents into a rotating reference frame using dq coordinates. Through this method, the field current (id) and torque-producing current (iq) can be adjusted separately, allowing for improved motor performance and precise control. This research aims to analyze the influence of the reference field current (ids*) on the performance of a three-phase induction motor using the FOC method. Simulation results indicate that increasing the value of ids* leads to a reduction in rotor speed. Moreover, changes in ids* significantly affect the motor's dynamic response, including the time required to reach steady-state conditions and the amount of overshoot in the system’s response. From the testing scenario with speed setpoints of 1000, 2000, and 3000 RPM, it was found that the FOC method, when combined with a PI (Proportional-Integral) controller, is capable of producing fast response times—up to 0.16 seconds rise time. Additionally, the PI controller plays a significant role in minimizing the overshoot, resulting in a stable and responsive speed control system for the induction motor.